PERANCANGAN STRATEGI PENGUATAN IMPLEMENTASI KEBIJAKAN REHABILITASI HUTAN DAN LAHAN STUDI KASUS DI DESA BANGUNJAYA, KECAMATAN CIGUDEG, KABUPATEN BOGOR, JAWA BARAT - Raditya Machdi Rachman; Arif Satria; Gendut Suprayitno (School of Business, Bogor Agricultural University (SB-IPB), 2016)
This study was conducted to measure the implementation gap of forest and land rehabilitation (RHL) policy against its objectives, namely maintaining life support systems, and designing strategies to strengthen its subsequent implementation. This study took a case study on the implementation of RHL at Bangunjaya Village, Cigudeg District of Bogor. The assessment used three parameters based on Permenhut No P.39/Menhu-II/2010 including regional, institutional, and technological parameters as well as community participation. Each parameter was weighed by the ranking method based on interviews with the experts. The strategy design was conducted using the Analytic Network Process (ANP). The research results showed that the level of successful implementation in Bangunjaya RHL is 66.3%, categorized as